Achieving high data rates through full duplex relaying in multicell environments. Issue 1 (24th February 2014) - Sharma, Prabhat Kumar; Garg, Parul
Abstract: In this paper, we investigate the outage and error performances of a full duplex relaying cooperative system in a multicell environment, considering the possibility of co‐channel interference from the users located in the nearby cells. The decode‐and‐forward cooperative strategy is assumed at the relay. Throughout the analysis, we consider all the channels to be independent but not necessarily identically distributed as generalised Nakagami‐ m fading. We find an accurate closed‐form expression of outage probability and average symbol error rate for integer values of fading parameter m . The analysis considers symmetric M ‐ary phase shift keying modulation scheme with equal energy constellation. Copyright © 2014 John Wiley & Sons, Ltd. Abstract : The outage and error performances are investigated for a full duplex decode and forward relaying in a hexagonal multicell environment. The possibility of co‐channel interference from the users located in the nearby cells is considered. For generalized Nakagami‐ m fading environment, accurate closed‐form expressions of outage probability and average symbol error rate are derived for M ‐ary phase shift keying.